Methodological design for structuring investment portfolios according to the risk profile of the investor - María Patricia Durango-Gutiérrez; Luis David Delgado-Vélez (CLIO América, 2017)
The high level of quantitative development that is being applied in the creation of investment portfolios in the financial market allows developing methodologies based on criteria and mathematical models adjusted to the economic reality that manages to minimize losses and obtain a greater economic benefit expected by the investor. The objective of the article is to define a methodology for the creation of an investment portfolio, according to the risk profile of the investor for portfolios with multiple assets and that, through value at risk, simulate the optimization of the portfolio and generate greater profitability. When determining that the portfolio is composed of shares of different Colombian companies and in different economic sectors, and through monitoring it allows incorporating an analysis of the financial risks to which investors are exposed, allowing to reduce the probability of loss that affects the equity or caused by changes and / or adverse movements in the risk factors that affect the price or final value.